The Impact of Financial Performance Indicators on the Market Value of Stocks (Case Study) (Journal of Hama University, 2020)
This research aimed to identify the impact of financial performance on the market value of the stocks of Syria International Islamic Bank during the period from 2010 to 2018, the financial performance of Syria International Islamic Bank which was studied by the following financial indicators: (profitability indicators:( by the return on assets (ROA), and the return on equity (ROE) ) , capital adequacy ratio, debt ratio, and liquidity ratio), and studying the effect of these indicators on the market value of stocks using the simple regression analysis to study the effect of independent variables represented by financial performance, In the dependent variable represented by the market value of the stocks by SPSS program , the results of the hypotheses test concluded that there is no statistically significant effect between the financial performance indicators by ( the return on assets - the rate of return on equity - the rate of capital adequacy) and the market value of stocks of Syria International Islamic Bank, while both the debt ratio and the liquidity ratio had a statistically significant effect on the market value of stocks of Syria International Islamic Bank.